Using Quality Improvement to Increase Access to Behavioral Health Care in Federally Qualified Health Centers - Alexandros Maragakis; Cassandra Snipes; Joseph Mazzucotelli; Charles Duarte (SAGE Publishing, 2015)
Objectives: Integrated care programs, in which behavioral health is integrated in primary care settings, have been widely implemented as solution to rising health care expenditures. A number of recommendations for implementation of integrated care have been published in the past decade; however, data regarding how to produce the most effective system are lacking. This may be because of the fact that existing integrated care programs do not institute quality improvement initiatives that could generate this needed data. Methods: A quality improvement program was instituted at an integrated Federally Qualified Health Center. As a result, productivity and no-show rates were analyzed for two psychology externs providing integrated care services. A process map was created to identify systematic methods to improve outcomes. Results: There were statistically significant increases to productivity increased and decreases no-show rates through systematic changes. Conclusion: This case study provides evidence that quality improvement systems in integrated care can result in systemic changes that improve access to care.